High-entropy alloy composite material for metal fuel cell and preparation method of high-entropy alloy composite material
By electrodepositing high-entropy alloy materials on the surface of carbon paper to form a high-entropy alloy composite with core-shell structure, the problems of long preparation period of high-entropy alloys, high energy consumption and high cost of precious metal catalysts are solved, and efficient electrocatalytic performance is achieved.
Patent Information
- Application Number
- CN202411935214.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-26
AI Technical Summary
In the prior art, the preparation method of high entropy alloys has a long period of time, high energy consumption and serious pollution, and the precious metal catalysts are costly and have poor stability, making them difficult to replace.
The electrochemical workstation was used to perform constant voltage electrodeposition, and the high-entropy alloy material NiFeCoZnCuMnCr was loaded on the surface of the treated carbon paper. By regulating the total concentration of the precursor solution and the proportion of metal salt, a high-entropy alloy composite material with a shell of polymetal hydroxide and a core-shell structure with a core-shell structure of a high-entropy alloy was optimized.
The high entropy alloy composite exhibits excellent electrocatalytic properties, with the overpotentials required for OER and HER to reach a current density of 100 mA cm-2 of 378 mV and 331 mV, respectively, overcoming the cost and stability of precious metal catalysts.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery energy, and in particular relates to a high entropy alloy composite material for metal fuel cells and a preparation method thereof. Background Art
[0002] With the rapid development of the economy and society, the global demand for energy is increasing. The extensive use of traditional energy sources such as coal and oil has caused serious environmental crises and climate deterioration. At present, solar energy, geothermal energy, wind energy and tidal energy are common and usable renewable clean energy sources for humans, but these high-quality renewable energy sources are affected by uncontrollable factors such as geography and seasons during their use, and their actual utilization rate is low. The energy density of hydrogen energy is as high as 142 MJ kg -1 , its high calorific value is second only to nuclear energy, which is several times that of fossil energy. In addition, the earth's hydrogen resources are abundant, and the final combustion product of hydrogen is only water, which is one of the most ideal clean energy sources. The three methods of hydrogen production from fossil fuels, water gas and methanol reforming account for 96% of industrial hydrogen production. However, traditional hydrogen production technology is limited by high cost, pollution, low yield and other problems. It is urgent to find a more green, environmentally friendly and efficient hydrogen production method. Photocatalytic and electrocatalytic water decomposition to produce hydrogen has gradually become a hot topic of research. Using inexhaustible solar energy, photocatalytic water decomposition to produce hydrogen is the most ideal means. However, due to cost and efficiency constraints, the practical application of photocatalytic hydrogen production is inevitably hindered. Compared with photocatalytic hydrogen production, electrocatalytic hydrogen production has many advantages, such as higher purity of prepared hydrogen and higher hydrogen production efficiency, which is a relatively more ideal hydrogen production method.
[0003] Electrocatalytic water splitting uses an applied voltage to provide energy. The electrocatalytic water splitting reaction includes two half reactions, oxygen evolution reaction and hydrogen evolution reaction, which produce O2 and H2 respectively. Under standard conditions, the thermodynamic equilibrium potential of OER is 1.23V, and the thermodynamic equilibrium potential of HER is 0 V. Due to unfavorable factors such as solution concentration polarization, solution resistance and interface resistance, electron transfer is hindered in the electrocatalytic water splitting reaction. In practical applications, the voltage required for OER and HER is higher than the thermodynamic equilibrium potential. This excess voltage is the overpotential. Both the OER and HER processes require efficient electrocatalysts to reduce the overpotential and improve the efficiency of water electrolysis. However, the catalysts with the best electrocatalytic water splitting performance are currently precious metals and their derivatives. RuO2 and IrO2 have the best OER catalytic performance, while Pt has the best HER catalytic performance. Limited by the cost and stability of precious metals, it is crucial to develop excellent and low-cost substitutes for precious metal catalysts.
[0004] Based on this, this application was developed. Summary of the invention
[0005] The present invention aims to solve the problems that most preparation methods of high entropy alloys have long production cycles, high energy consumption and serious pollution, and provides a high entropy alloy composite material for metal fuel cells. The high entropy alloy composite material overcomes the defects of the prior art, significantly improves catalytic performance, and exhibits excellent electrocatalytic performance.
[0006] The present invention also provides a method for preparing the high entropy alloy composite material for metal fuel cells under normal temperature and pressure conditions.
[0007] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a high entropy alloy composite material for a metal fuel cell comprises the following steps: 1) Pre-treating the carbon paper; 2) Preparing a precursor solution: using N,N-dimethylformamide (DMF) and acetonitrile (CH3CN) as solvents, adding a surfactant and a metal chloride salt, and mixing by magnetic stirring at room temperature to obtain a precursor solution; the metal chloride salt is composed of a mixture of nickel chloride hexahydrate NiCl2·6H2O, anhydrous iron chloride FeCl3, cobalt chloride hexahydrate CoCl2·6H2O, copper chloride dihydrate CuCl2·2H2O, anhydrous zinc chloride ZnCl2, manganese chloride tetrahydrate MnCl2·4H2O, and chromium chloride tetrahydrate CrCl2·4H2O; 3) The precursor solution is transferred to the electrolytic cell, and the appropriate deposition voltage and deposition time are selected according to the specific experimental requirements. The high entropy alloy composite material loaded on the carbon paper is prepared by electrodeposition. After the deposition is completed, the deposition product is washed and dried. The prepared sample can be directly subjected to electrochemical testing.
[0008] Specifically, in the precursor solution of step (2), the molar ratio of nickel chloride hexahydrate, anhydrous ferric chloride, cobalt chloride hexahydrate, anhydrous zinc chloride, cupric chloride dihydrate, manganese chloride tetrahydrate, and chromium chloride tetrahydrate includes but is not limited to 1:5-15:5-15:3:1:1:1.
[0009] Specifically, in the precursor solution of step (2), the total concentration of the metal chloride salt can be 0.07-0.35 mol L -1 More preferably, the total concentration of the metal chloride is 0.15-0.25 mol L -1 The molar ratio of metal elements is further preferably Ni:Fe:Co:Zn:Cu:Mn:Cr=1:5:15:3:1:1:1.
[0010] Specifically, in step (2), the surfactant used may be polymethyl methacrylate (PMMA) or glucose (GLU), and the concentration of the surfactant in the precursor solution may be 5-10 g L-1 For example, the surfactant used may be at a concentration of 5 g L -1 of polymethyl methacrylate or 5 g L -1 The volume ratio of N,N-dimethylformamide to acetonitrile can be 3-5:1.
[0011] Specifically, in step (1), the carbon paper is cut into small pieces, soaked in hydrochloric acid and then ultrasonically treated, rinsed with deionized water; ultrasonically treated with acetone and then rinsed with deionized water; ultrasonically treated with deionized water and then rinsed with anhydrous ethanol, and vacuum dried to obtain a deposition carrier carbon paper. 2 Carbon paper with 2-4 mol L -1 Soak in hydrochloric acid for 12-36 h, ultrasonicate for 15-45 min, and vacuum dry in a vacuum oven at 40-70℃ for 1-3 h.
[0012] Specifically, in step (3), the carbon paper substrate can be used as the working electrode, the carbon rod can be used as the counter electrode, and the mercury-mercury oxide electrode can be used as the reference electrode; the carbon paper substrate and the carbon rod electrode are placed facing each other with a distance of 1-2 cm between them. The deposition voltage can be -2 to -3 V, and the deposition time can be 1600-2000 s. The loading area is preferably 0.5 cm 2 .
[0013] The present invention provides a high entropy alloy composite material for a metal fuel cell obtained by the above-mentioned preparation method.
[0014] The present invention also provides the use of the high entropy alloy composite material for metal fuel cells in the electrolysis of water to produce hydrogen.
[0015] The present invention uses an electrochemical workstation to perform constant voltage electrodeposition on the treated carbon paper surface to load the high entropy alloy material NiFeCoZnCuMnCr, explores the influence of various factors on the performance and morphology of the high entropy alloy composite material, and finds the optimal preparation conditions of the high entropy alloy composite material. By adjusting the total concentration of the precursor solution to 0.21 mol L -1 The core-shell high entropy alloy composite material with a multimetal hydroxide (NiFeCoZnCuMnCr)LDH shell and a high entropy alloy NiFeCoZnCuMnCr HEAs core was synthesized with a metal salt ratio of Ni:Fe:Co:Zn:Cu:Mn:Cr =1:5:15:3:1:1:1. The OER and HER of the high entropy alloy composite material reached 100 mA cm -2 The overpotential required for the current density is 378 mV and 331 mV, respectively, showing excellent electrocatalytic performance. Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: 1) The present invention uses an electrochemical workstation to perform constant voltage electrodeposition and explores the effects of various factors on the performance and morphology of high entropy alloy catalysts.
[0016] 2) The present invention further optimizes and synthesizes a high-entropy alloy composite material with a core-shell structure in which the outer shell is a polymetallic hydroxide and the inner core is a high-entropy alloy by regulating the total concentration of the precursor and the ratio of the metal salt. As the types and quantities of the components increase, the number of active sites of the high-entropy alloy composite material also increases accordingly, so that the high-entropy alloy composite material has excellent OER and HER dual-functional catalytic activity and can be used for water electrolysis to produce hydrogen. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 XRD patterns of the high entropy alloy composite materials prepared in Examples 1, 2, and 3; Figure 2 SEM images of catalysts with different total precursor concentrations (a) total precursor concentration 0.07 mol L-1; (b) total precursor concentration 0.21 mol L-1; (c) total precursor concentration 0.35 mol L-1; Figure 3 SEM images of different Fe:Co high entropy alloy composites (a) Example 1 Fe:Co=1:3; (b) Example 2 Fe:Co=1:1; (c) Example 3 Fe:Co=3:1; Figure 4 TEM image (a) of the Fe:Co=1:3 high entropy alloy composite material of Example 1; high magnification TEM image (b); (c) SAED image of the shell; Figure 5 OER (a) and HER LSV (b) curves of high entropy alloy composites prepared with different additives; Figure 6 Electrochemical test results of different materials (a) OER LSV curve; (b) HER LSV curve; (c) OER Tafel curve; (d) HER Tafel curve; (e) double layer capacitance Cdl; (f) Nyquist diagram; Figure 7 It is the it test curve of the Fe:Co=1:3 high entropy alloy composite material in Example 1; Figure 8 This is the full water decomposition curve of the Fe:Co=1:3 high entropy alloy composite material in Example 1 before and after it test, and the built-in illustration is the actual picture of electrolyzed water. DETAILED DESCRIPTION
[0018] The technical solution of the present invention is further described in detail below in conjunction with embodiments, but the protection scope of the present invention is not limited thereto.
[0019] In the following examples, the raw materials used are all common commercial products that can be directly purchased or can be prepared using conventional techniques in the art.
[0020] Room temperature refers to 25±°C.
[0021] Example 1 A method for preparing a high entropy alloy composite material comprises the following steps: (1) Cut the carbon paper into 0.5×1 cm pieces 2 small pieces, using 3 mol L -1 The carbon paper was soaked in hydrochloric acid for 24 h, then ultrasonicated for 30 min, and rinsed with deionized water for 3 to 5 times after the ultrasonication. Then, the carbon paper was ultrasonicated with acetone for 30 min, and rinsed with deionized water for 3 to 5 times. Then, the carbon paper was ultrasonicated with deionized water for 30 min, and rinsed with anhydrous ethanol for 3 to 5 times. The carbon paper was dried in a vacuum oven at 60 °C for 2 h to obtain the deposited carrier carbon paper.
[0022] (2) All chemical raw materials can be used directly without any processing. In the process of preparing the precursor solution, 20 ml of N,N-dimethylformamide and 5 ml of acetonitrile were measured as solvents, and polymethyl methacrylate was weighed and added as a surfactant (concentration of 5 g L -1 ), and then add nickel chloride hexahydrate, (anhydrous ferric chloride + cobalt chloride hexahydrate), anhydrous zinc chloride, cupric chloride dihydrate, manganese chloride tetrahydrate and chromium chloride tetrahydrate in a molar ratio of 1:20:3:1:1:1, where the molar ratio of Fe to Co is 1:3, and the total concentration of metal salts is 0.21 mol L -1 , and then magnetically stirred at room temperature for 2 h to mix evenly to obtain a precursor solution.
[0023] (3) The precursor solution was transferred to an electrolytic cell, with the carbon paper substrate as the working electrode, the carbon rod as the counter electrode, and the mercury-mercury oxide electrode as the reference electrode. The carbon paper substrate and the carbon rod electrode were placed facing each other with a distance of 1 cm between them for electrodeposition. The deposition voltage was -2.5 V and the deposition time was 1800 s. After the deposition was completed, the deposited product was rinsed with deionized water for 3 to 5 times, then rinsed with anhydrous ethanol for 3 to 5 times, and vacuum dried at 60 ° C for 2 h to obtain a high entropy alloy composite material loaded on carbon paper. The prepared sample can be directly subjected to electrochemical testing.
[0024] Example 2 The preparation process is similar to that of Example 1, except that the molar ratio of Fe and Co added is 1:1.
[0025] Example 3 The preparation process is similar to that of Example 1, except that the molar ratio of Fe to Co added is 3:1.
[0026] Example 4 The preparation process is similar to that of Example 1, except that the constant voltage electrodeposition is changed to pulse electrodeposition. The pulse electrodeposition applies a specific current for 0.2 s, then turns off the current for 0.8 s, with one second as one cycle. The current density applied for the pulse deposition is 8-64 mA cm -2 .
[0027] Comparative Example 1 The preparation process was the same as in Example 1, except that the total concentration of the metal salt was 0.07 mol L -1 .
[0028] Comparative Example 2 The preparation process is the same as in Example 1, except that the total concentration of the metal salt is 0.35 mol L -1 .
[0029] Comparative Example 3 The preparation process is the same as that of Example 1, except that polymethyl methacrylate is not added as a surfactant.
[0030] Comparative Example 4 The preparation process is the same as in Example 1, except that glucose is added as a surfactant.
[0031] Comparative Example 5 The preparation process is the same as that of Example 1, except that manganese chloride tetrahydrate and chromium chloride tetrahydrate are not added, and the composite material is recorded as a five-element high entropy alloy composite material.
[0032] Comparative Example 6 The preparation process is the same as that of Example 1, except that manganese chloride tetrahydrate, chromium chloride tetrahydrate and surfactant polymethyl methacrylate are not added, and it is recorded as five-element high entropy alloy composite material + no additive.
[0033] Microstructure and electrochemical performance 1. Structural characterization The phase composition of high entropy alloy composites was characterized by XRD. Figure 1 As shown in the figure, it can be seen that the high entropy alloy composite materials prepared in Examples 1 to 3 have no obvious alloy diffraction peaks, the XRD diffraction patterns are the same as those of pure carbon paper (CP), and the high entropy alloy composite materials are amorphous structures.
[0034] SEM was used to characterize the basic morphological characteristics of high entropy alloy composites. Figure 2 Example 1 (0.21 mol L -1 , Fe:Co=1:3), Comparative Example 1 (0.07 mol L-1 , Fe:Co=1:3) and Comparative Example 2 (0.35 mol L -1 , Fe:Co=1:3) SEM morphology. It can be seen from the figure that: at 0.07 mol L -1 At 0.21 mol L -1 At 0.35 mol L -1 At the highest concentration, the overall particle size is the largest, and there is no flocculent material on the particle surface, but there seems to be a layer of thin film material on the catalyst surface.
[0035] Figure 3 The SEM images of different Fe:Co high entropy alloy composite materials of Examples 1 to 3 are given. It can be seen from the figure that: Example 1 (0.21 mol L -1 , Fe:Co=1:3) and Example 2 (0.21 mol L -1 , Fe:Co=1:1) is granular, while Example 3 (0.21 mol L -1 , Fe:Co=3:1) samples have larger flake structures. Flocculent or flake-like substances appear on the catalyst surface at these three ratios, but only Example 1 (0.21 mol L -1 , Fe:Co=1:3) is covered by dense and uniform flake structures, forming a core-shell structure. Combining the XRD results with the surface morphology, it is speculated that the amorphous structure of the high-entropy alloy composite material under the experimental conditions is related to the flocculent or flake substances appearing on the surface of the material. The flocculent or flake substances are amorphous structures, so the material also presents an amorphous structure.
[0036] TEM was used to further study the microstructure of the high entropy alloy composite material. Figure 4 As shown in 4(a), it can be seen that Example 1 (0.21 mol L -1 , Fe:Co=1:3) part of the morphology shows a typical lamellar hydrotalcite structure. In 4 (b) high-magnification TEM, lattice fringes with interplanar spacing of 0.1811 nm and 0.2399 nm were observed, corresponding to the (102) and (101) planes of the Co(OH)2 crystal structure, respectively. However, the lattice fringes are few and unclear. Figure 4 (c) is the selected electron diffraction pattern (SAED) of this part. The diffraction rings in this part are weak, which is consistent with the small and unclear lattice fringes, and also indicates that the crystallinity of this part of the material is weak.
[0037] 2 Electrochemical performance The OER and HER performance tests were performed using an electrochemical workstation (CHI 760E). The test used a three-electrode system, with the high-entropy alloy composite material deposited on carbon paper as the working electrode, the counter electrode as a carbon rod, the reference electrode as mercury-mercuric oxide, and the electrolyte as 1 mol L -1 The linear sweep voltammetry (LSV) test was preceded by cyclic voltammetry (CV) activation, with a CV activation scan rate of 5 mV s -1 The voltage range was 0–1 V, the scan was 20 cycles, and the scan rate for OER and HER tests was 5 mV s -1 CV activation can ensure that the catalyst performance is in a relatively stable state. It is uniformly stipulated here that the overpotentials of OER and HER described below are all when the current density reaches 100 mA cm -2 The overpotential at .
[0038] In order to study the effect of additives on the properties of high entropy alloy composites, the present invention uses 1 mol L -1 The OER and HER performances of high entropy alloy composites synthesized with PMMA as an additive, GLU as an additive, and without additives were tested in a KOH solution using a three-electrode system. Figure 5 It can be seen that the high entropy alloy composite material synthesized with PMMA as an additive has the best OER and HER performance, and its OER and HER reach 100 mA cm -2 The overpotentials required for the current density are 378 mV and 331 mV, respectively. Suitable additives such as PMMA can make the catalyst more firmly loaded on the carbon paper carrier, enhance the bonding force between the catalyst and the matrix, improve the stability of the catalyst, improve the catalytic activity of the catalyst, and enhance the electrochemical performance.
[0039] To further prove that the seven-element high entropy alloy composite material has excellent OER and HER performance, the present invention compares the performance of commercial platinum-carbon catalyst (Pt / C), five-element high entropy alloy composite material, and seven-element high entropy alloy composite material synthesized by constant pressure and pulse electrodeposition. The results are shown in Figure 6 In 1 mol L -1 The OER and HER performance, electrochemical active area and electrochemical impedance spectroscopy of the materials were tested in KOH solution. The OER and HER polarization curves of each catalyst are shown in Figure 2. Figure 6 As shown in (a) and (b), the seven-element high entropy alloy composite material has the best overall catalytic performance, with OER and HER overpotentials of 378 mV and 331 mV, respectively. Figure 6(c) The Tafel slopes of the four catalysts during the OER reaction. The Tafel slopes are ranked from high to low as follows: quinary high entropy alloy composite material + no additive (286.48 mV dec -1 )>Five-element high entropy alloy composite material(103.26 mV dec -1 )>Seven-element high entropy alloy composite prepared by pulse electrodeposition (49.98 mV dec -1 )>Seven-element high entropy alloy composites prepared by constant voltage electrodeposition (45.63 mV dec -1 ). Figure 6 (d) Tafel slopes of the four catalysts during the HER reaction. The slopes are ranked from high to low as follows: five-element high entropy alloy composite material + no additive (165.81 mV dec -1 )>Five-element high entropy alloy composite material(135.52 mV dec -1 )>Seven-element high entropy alloy composite prepared by pulse electrodeposition (75.53 mV dec -1 )>Seven-element high entropy alloy composites prepared by constant voltage electrodeposition (48.14 mV dec -1 ), the seven-element high entropy alloy composite material prepared by constant voltage electrodeposition has the lowest Tafel slope in both OER and HER reactions, indicating that the catalyst has a faster reaction kinetics and better catalytic activity. The double layer capacitance (Cdl) was then calculated using the CV curve within the non-Faraday voltage range. Since the double layer capacitance (Cdl) is positively correlated with the electrochemical activation area (ECSA), the relative size of the ECSA can be compared by calculating Cdl. The Cdl results of the four high entropy alloy composite materials are shown in Figure 2. Figure 6 As shown in (e), the double layer capacitances of the five-component high entropy alloy composite material + no additive, the seven-component high entropy alloy composite material prepared by pulse electrodeposition, the five-component high entropy alloy composite material, and the seven-component high entropy alloy composite material prepared by constant voltage electrodeposition are 0.32 mF cm -2 , 0.45 mF cm -2 、23.91 mF cm -2 and 47.93 mF cm -2 The seven-element high entropy alloy composite material prepared by constant voltage electrodeposition has the largest double-layer capacitance, corresponding to the largest electrochemical active area ECSA. The larger the ECSA of the catalyst, the more active sites are exposed during the electrocatalytic process, and the better the catalytic activity. It can be seen that the increase in active sites is the main reason why the seven-element high entropy alloy composite material has better performance than the five-element high entropy alloy composite material. The electrochemical impedance spectroscopy test was carried out on the four materials. The test structure is as follows: Figure 6As shown in (f), the seven-element high entropy alloy composite materials prepared by constant voltage electrodeposition and pulse electrodeposition have a relatively small semicircle radius of the Nyquist circle. The smaller the radius, the smaller the impedance, the higher the electron transfer efficiency, and the faster the reaction rate. The reason why these two materials have smaller impedance is that the seven-element high entropy alloy composite material alloy itself has good electrical conductivity.
[0040] In order to verify that the seven-element high entropy alloy composite material has good electrolysis performance stability, the seven-element high entropy alloy composite material was subjected to a chronoamperometry stability test (IT). The longer the discharge time at a constant voltage, the smaller the change in current density, and the better the stability of the catalyst. Figure 7 As shown in the figure, constant voltage discharge was carried out at a voltage of 0.75 V. The current density retention rate was 89.04% after constant voltage discharge for 70 h. The current density changed little with time, which proved the excellent long-term stability of the high entropy alloy composite material.
[0041] In order to prove that the seven-element high entropy alloy composite material has excellent electrolytic water splitting performance, based on the excellent OER and HER bifunctional catalytic activity of the seven-element high entropy alloy composite material, the seven-element high entropy alloy composite material was used as the anode and cathode to produce hydrogen and oxygen in the complete water splitting under an applied voltage. -1 The water splitting performance was tested in KOH. Figure 8 As shown, the current density reaches 50 mA cm at room temperature. -2 When the voltage is 1.784 V, the actual picture of water electrolysis is as follows Figure 8 As shown in the built-in illustration, H2 bubbles are generated at the cathode and O2 bubbles are generated at the anode. At the same time, the full water splitting performance of the seven-element high entropy alloy composite material after the stability test is tested. After the test, the seven-element high entropy alloy composite material reaches 50 mA cm -2 The voltage required for the current density is 1.851V. After the chronoamperometry stability test, the full water splitting performance decreased, but the change was not significant, proving that the seven-element high entropy alloy composite material has excellent water electrolysis performance.
[0042] In summary, the seven-element high entropy alloy composite material prepared by constant voltage electrodeposition and regulating the total concentration of the precursor solution and the ratio of the metal salt has excellent OER and HER performance. Compared with the five-element high entropy alloy composite material, the seven-element high entropy alloy composite material has faster electrochemical reaction kinetics, larger electrochemical active area, more active sites and higher electrical conductivity. The seven-element high entropy alloy composite material showed good stability, and the current density retention rate was 89.04% after 70 h of it test. At 1 mol L -1 In KOH solution, the complete water decomposition curve of the seven-element high entropy alloy composite material reaches 50 mA cm -2The voltage required for the current density is 1.851 V, which fully proves that the seven-element high-entropy alloy composite material is an excellent water electrolysis catalyst.
Claims
1. A method for preparing a high entropy alloy composite material for a metal fuel cell, characterized in that: The steps include: 1) Pre-treating the carbon paper; 2) Preparing a precursor solution: using N,N-dimethylformamide and acetonitrile as solvents, adding a surfactant and a metal chloride salt, and mixing well to obtain a precursor solution; the metal chloride salt is composed of a mixture of nickel chloride hexahydrate, anhydrous ferric chloride, cobalt chloride hexahydrate, copper chloride dihydrate, anhydrous zinc chloride, manganese chloride tetrahydrate, and chromium chloride tetrahydrate; 3) The precursor solution is transferred to an electrolytic cell, and a suitable deposition voltage and deposition time are selected to prepare a high entropy alloy composite material loaded on carbon paper by electrodeposition. After the deposition is completed, the deposited product is washed and dried.
2. The method for preparing a high entropy alloy composite material for a metal fuel cell according to claim 1, characterized in that: In the precursor solution of step (2), the molar ratio of nickel chloride hexahydrate, anhydrous ferric chloride, cobalt chloride hexahydrate, anhydrous zinc chloride, cupric chloride dihydrate, manganese chloride tetrahydrate and chromium chloride tetrahydrate is 1:5-15:5-15:3:1:1:
1.
3. The method for preparing a high entropy alloy composite material for a metal fuel cell according to claim 1, characterized in that: In step (2), the surfactant used is polymethyl methacrylate or glucose, and the concentration of the surfactant in the precursor solution is 5-10 g L -1 .
4. The method for preparing a high entropy alloy composite material for a metal fuel cell according to claim 1, characterized in that: In step (1), the carbon paper is soaked in hydrochloric acid, ultrasonically treated, and then rinsed with deionized water; ultrasonically treated with acetone and then rinsed with deionized water; ultrasonically treated with deionized water and then rinsed with anhydrous ethanol, and vacuum dried to obtain a deposited carrier carbon paper.
5. The method for preparing a high entropy alloy composite material for a metal fuel cell according to claim 4, characterized in that: In step (1), carbon paper is treated with 2-4 mol L -1 Soak in hydrochloric acid for 12-36 h, ultrasonicate for 15-45 min, and vacuum dry in a vacuum oven at 40-70℃ for 1-3 h.
6. The method for preparing a high entropy alloy composite material for a metal fuel cell according to claim 1, characterized in that: In step (3), the carbon paper substrate is used as the working electrode, the carbon rod is used as the counter electrode, and the mercury-mercury oxide electrode is used as the reference electrode; the carbon paper substrate and the carbon rod electrode are placed facing each other with a distance of 1-2 cm between them.
7. The method for preparing a high entropy alloy composite material for a metal fuel cell according to claim 1, characterized in that: In step (3), the deposition voltage is -2 ~ -3V, and the deposition time is 1600-2000 s.
8. A high entropy alloy composite material for a metal fuel cell obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the high entropy alloy composite material for metal fuel cells according to claim 8 in producing hydrogen by electrolysis of water.
Citation Information
Patent Citations
High-entropy alloy porous electrode and preparation method thereof
CN112609213A
High-entropy alloy loaded activated carbon catalyst for acetylene hydrochlorination reaction, and preparation method and application thereof
CN113209971A
High-entropy alloy and preparation method thereof, membrane electrode assembly and fuel cell
CN116574957A
Preparation method of non-noble metal high-entropy alloy composite material with core-shell structure
CN117702213A
Electrode catalyst for fuel cells, method for producing the same, and electrode for fuel cells
JP2009208070A
Cited By
High-entropy alloy electrocatalyst with core-shell structure as well as preparation method and application of high-entropy alloy electrocatalyst
CN120400899A